PERKEMBANGAN METODOLOGI PENELITIAN HUKUM - Muhdlor, Ahmad Zuhdi (Jurnal Hukum dan Peradilan, 2012)
Doctrinal research asks what the law is on a particular issue. It is concerned with analysis of the legal doctr ine a nd how i t ha s been developed a nd a ppl ied. This type of r esea r ch is a lso known a s pur e theoretical research. It consists of either a simple research directed at finding a specific statement of the law or a more complex and in depth analysis of legal reasoning. Non-doctrinal research, also known as socio-legal research is a legal research that employs methods ta ken fr om other discipl ines to gener a te empir ica l da ta to a nswer r esea r ch quest ions. It ca n be a problem, policy or law reform based. Nondoctrinal legal research can be qualitative or quantitative. Doctrinal and nondoctrinal research could be part of a large scale project. Non-doctrinal approach allows the researcher to perform inter disciplinary research where he analyses law from the perspective of other sciences and employs these sciences in the formulation of the law. Keyword: Doctrinal research, Theoretical research, Law